Brain sources' activity in resting state before a visuo-motor task. (17th March 2021) - Miraglia, Francesca; Vecchio, Fabrizio; Alù, Francesca; Orticoni, Alessandro; Judica, Elda; Cotelli, Maria; Rossini, Paolo Maria
Abstract: Objective. In modern neuroscience, the underlying mechanisms of the elaboration and reaction to different kinds of stimuli of the brain hemispheres remain still very challenging to understand, together with the possibility to anticipate certain behaviors to improve the performance. Approach. The purpose of the present study was to investigate the brain rhythms characteristics of electroencephalographic (EEG) recordings and in particular, their interhemispheric differences in resting state condition before a visuo-motor task in a population of healthy adults. During the task, subjects were asked to react to a sequence of visual cues as quick as possible. The reaction times (RTs) to the task were measured, collected and correlated with the EEG signals recorded in a resting state condition immediately preceding the task. The EEG data were analyzed in the space of cortical sources of EEG rhythms by the computation of the global spectra power density (GSPD) in the left and in the right hemisphere, and of an index of brain laterality ( L ). Main results. The results showed a negative correlation between the RTs and the GSPD in the central areas in the left and in the right hemisphere in both eyes open (EO) and eyes closed (EC) conditions. A close to significant and negative correlation was found in the parietal areas. Furthermore, RTs negatively correlated with L in the central areas in EC condition. The results showed a negative correlation between the RTs and the GSPD in the central areas in the left and in the right hemisphere in both EO and EC conditions. Significance. The correlations between the brain activity before a task and the RTs to the task can represent an interesting tool for exploring the brain state characterization for the upcoming tasks performance.